Identifying the most significant indicators of the total road safety performance index. (April 2018) - Tešić, Milan; Hermans, Elke; Lipovac, Krsto; Pešić, Dalibor
Highlights: Small number of key RSPI is an efficient way of monitoring. An index (RSPIln n ) is calculated using a limited number of indicators. RSPIln n is reliable and robust enough to enable earlier goal-oriented actions. Abstract: The review of the national and international literature dealing with the assessment of the road safety level has shown great efforts of the authors who tried to define the methodology for calculating the composite road safety index on a territory (region, state, etc.). The procedure for obtaining a road safety composite index of an area has been largely harmonized. The question that has not been fully resolved yet concerns the selection of indicators. There is a wide range of road safety indicators used to show a road safety situation on a territory. Road safety performance index (RSPI) obtained on the basis of a larger number of safety performance indicators (SPIs) enable decision makers to more precisely define the earlier goal- oriented actions. However, recording a broader comprehensive set of SPIs helps identify the strengths and weaknesses of a country's road safety system. Providing high quality national and international databases that would include comparable SPIs seems to be difficult since a larger number of countries dispose of a small number of identical indicators available for use. Therefore, there is a need for calculating a road safety performance index with a limited number of indicators (RSPIln n ) which will provide a comparison of a sufficient quality, of as many countries as possible. The application of the Data Envelopment Analysis (DEA) method and correlative analysis has helped to check if the RSPIln n is likely to be of sufficient quality. A strong correlation between the RSPIln n and the RSPI has been identified using the proposed methodology. Based on this, the most contributing indicators and methodologies for gradual monitoring of SPIs, have been defined for each country analyzed. The indicator monitoring phases in the analyzed countries have been defined in the following way: Phase 1- the indicators relating to alcohol, speed and protective systems; Phase 2- the indicators relating to roads and Phase 3- the indicators relating to trauma management. This will help achieve the standardization of indicators including data collection procedures and selection of the key list of indicators that need to be monitored. Based on the results, it has been concluded that the use of the most contributing indicators will make it possible to assess the level of road safety on a territory, with an acceptable quality score by focusing on the low-ranked countries. A smaller set of significant indicators defined in this manner can serve for a fast and simple understanding of a road safety situation and assessment of effects of measures undertaken. Also, this universal index approach is applicable in cases when a broader comprehensive set of indicators is analyzed, which provides a more accurate identification of weaker points and rank the countries in a more meaningful way.